2017
DOI: 10.1159/000471924
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Perspectives on Metabolism, Survival Strategies, and Biotechnological Applications of <b><i>Brettanomyces bruxellensis</i></b> LAMAP2480

Abstract: Wine production is an important commercial issue for the liquor industry. The global production was estimated at 275.7 million hectoliters in 2015. The loss of wine production due to Brettanomyces bruxellensis contamination is currently a problem. This yeast causes a “horse sweat” flavor in wine, which is an undesired organoleptic attribute. To date, 6 B. bruxellensis annotated genome sequences are available (LAMAP2480, AWRI1499, AWRI1608, AWRI1613, ST05.12/22, and CBS2499), and whole genome comparisons betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…HPU technology was already tested for inactivation of the AWRI 1499 strain. 25 Godoy et al 43 reported that genomic characteristics related to the high tolerance to stress are distributed in the genome of the CBS 2499 strain as well as the AWRI 1499 strain of B. bruxellensis yeast. Therefore, in this research, we have focused on application of HPU for inactivation of the CBS 2499 strain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…HPU technology was already tested for inactivation of the AWRI 1499 strain. 25 Godoy et al 43 reported that genomic characteristics related to the high tolerance to stress are distributed in the genome of the CBS 2499 strain as well as the AWRI 1499 strain of B. bruxellensis yeast. Therefore, in this research, we have focused on application of HPU for inactivation of the CBS 2499 strain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In terms of non-thermal technologies, it has already been demonstrated that HHP inactivation efficiency strongly depends on the yeast strain used, wherein AWRI 1499 was more resistant than AWRI 1608 and AWRI 1613 (van Wyk and Silva, 2017a). Although analyses regarding high tolerance to stress showed that genomic characteristics are distributed in the genome of both CBS 2499 and AWRI 1499 strains (Godoy et al, 2017), it is possible that CBS 2499 could be more resistant to HHP treatments. However, before making any general conclusions it is necessary to conduct further, more extensive studies.…”
Section: Long-term Effect Of Hhpmentioning
confidence: 99%
“…Thereafter, the genomes of other B. bruxellensis strains were sequenced: (i) CBS2796 (ATCC 52904) strain, isolated from sparkling wine, with a genome length of 11.77 Mb [38]; (ii) UMY321 strain (corresponding to L17) [22] recognized to be diploid, with 82,632 SNPs revealing a high level of heterozygosity [39,40]; (iii) LAMAP2480 strain, with the largest genome found so far (26.99 Mb), has been the subject of study focusing on its spoilage role and biotechnological potential. The genome analysis showed the presence of several genes related to stress tolerance, nutrient uptake, ethanol production, and lignocellulose assimilation [41]; and (iv) UCD 2041 strain isolated from fruit wine, the DNA sequence of which was compared with strains belonging to different Brettanomyces species, such as B. nanus CBS1945, B. anomala CBS8139, B. naardenensis CBS6042, and B. custersianus CBS4805, revealing a large genetic distance within the genus. Moreover, relevant marker genes of domestic adaptation and fermentation were identified in UCD 2041, CBS1945, and CBS8139.…”
Section: Development Of Molecular Tools For the Genetic Modification Of B Bruxellensismentioning
confidence: 99%